Selection of Electronic Information Resources - Al, Umut; Al, Pınar (Information World, 2003)
For many years, library users have used only from the printed media in order to get the information that they have needed. Today with the widespread use of the Web and the addition of electronic information resources to library collections, the use of information in the electronic environment as well as in printed media is started to be used. In time, such types of information resources as, electronic journals, electronic books, electronic encyclopedias, electronic dictionaries and electronic theses have been added to library collections. In this study, selection criteria that can be used for electronic information resources are discussed and suggestions are provided for libraries that try to select electronic information resources for their collections.